Towards effective advertising regulation: A comparison of UK, Australian and South African schemes - D. Harker; S. Cassim (South African Journal of Business Management, 2002)
The regulation of advertising is a controversial and difficult process, and many schemes around the world opt for a self-regulatory approach to curb unacceptable advertising. However, when schemes are established or reformulated, most countries learn from other, more established, regimes. Whilst Australia and South Africa commenced the advertising self-regulation (ASR) process at similar times and based their systems on the UK model, two attempts have been made in Australia over the past three decades to produce more acceptable ads, whilst South Africa's system has endured in its original form. This paper reviews the ASR systems in these three countries, using a macro framework for analysis which contextualises advertising in society. The systems have the fundamental process of handling complaints about advertising in common, however there are advantages and disadvantages of each and these are discussed with a view to providing some guidance for Australia's fledgling, reformulated, system. Important insights for the development of regulation of advertising are presented.
Keywords: 650